ASEAN-CANADA FREE TRADE AGREEMENT: POTENTIAL ECONOMIC FOR ASEAN MEMBER COUNTRIES - Indanazulfa Qurrota A'yun (Universitas Ahmad Dahlan, 2020)
ASEAN and Canada agreed to establish cooperation as ASEAN-Canada Free Trade Agreement (FTA). This cooperation aims to strengthen economic relations between ASEAN and Canada by eliminating tariff barriers for almost all of trade in goods. Therefore, this study aims to calculate how big the effect of the ASEAN-Canada FTA trade agreement on the macroeconomic conditions of ASEAN member countries. The analysis method used is Computable General Equilibrium (CGE) model using Global Trade Analysis Project (GTAP) version 9A. This cooperation is expected to reduce trade barriers in all sectors, particularly tariff reductions as a representation of declining trade barriers in both ASEAN and Canada. This study analyse two trade policy scenarios by 50% and 100% (full liberalization) tariff reduction. The simulation results show that all ASEAN member countries get the benefit from full liberalization or a 50% tariff reduction on welfare except Laos and Philippines. In addition, this cooperation also can increase the real GDP in all ASEAN member countries and trade balance for Indonesia, Philippines, Singapore, Myanmar and Canada. It also has negative impacts on inflation and investment for some ASEAN member countries such as Brunei Darussalam, Cambodia, Laos, Malaysia and Thailand.